Neuroblastic Tumors of the Adrenal Gland in Elderly Patients: A Case Report and Review of the Literature - Deslarzes, Philip; Djafarrian, Reza; Matter, Maurice; La Rosa, Stefano; Gengler, Carole; Beck-Popovic, Maja; Zingg, Tobias (Frontiers in Pediatrics, 2022)
Abstract Background Neuroblastic neoplasms (NN) include ganglioneuromas (GN), ganglioneuroblastomas (GNB), and neuroblastomas (NB). They generally arise in childhood from primitive sympathetic ganglion cells. Their incidence in adults, especially among elderly, is extremely low. Case presentation This is the case of a 74-year-old woman with history of abdominal pain, weakness and night sweating since several months. Blood pressure was normal. CT-scan showed a 10 cm left adrenal mass, without other pathologic findings. An open left-sided adrenalectomy was performed. Recovery was uneventful with hospital length of stay of 8 days. Based on morphological, immunohistochemical, and molecular features the diagnosis was a nodular GNB. A positron emission tomography (PET) performed six weeks after the resection did not show any residual tumor or distant metastases. The patient was followed-up with annual clinical and radiological exams. Conclusion This case presentation, associated with a review of the literature, illustrates the importance to include GNB NN in the preoperative differential diagnosis of adrenal tumors in adults and highlights the need for multidisciplinary patient work-up and management. Keywords Neuroblastic tumor; adrenocortical tumor; ganglioneuroblastoma; case report; elderly patient; preoperative diagnosis; surgical and medical treatment; staging; ; follow-up List of abbreviations Alpha-Thalassemia Mental Retardation-X (ATRX), Dehydroepiandrosterone (DHEA), Cluster of Differentiation - 99 (CD99), Fluorodeoxyglucose (FDG) Ganglioneuromas (GN), Ganglioneuroblastomas (GNB), General Practician (GP) Glial Fibrillary Acidic Protein (GFAP), Metaiodobenzylguanidine (MIBG), International Neuroblastoma Staging System (INSS), International Neuroblastoma Risk Group Staging System (INRGSS), Neuroblastic Neoplasms (NN), Neuroblastomas (NB), Microtubule Associated Protein 2 (MAP-2), 3Myelocytomatosis oncogene (MYC), Overall Survival (OS), Positron Emission Tomography (PET), Splicing Factor 1 (SF1), Succinate Dehydrogenase (SDHB